Removal of Pb(II) using alginate – immobilized Myriophyllum spicatum beads - Milojković, Jelena; Stojanović, Mirjana; Mihajlović, Marija; Lopičić, Zorica (European Journal of Sustainable Development, 2016)
Directive 1999/31/EC requires that biowaste with more than 3% organic content isn’t accepted for landfilling directing toward more efficient use of biological material from the landfill. Myriophyllum spicatum is an aquatic weed which grows on every continent except Antarctica and it is noted for its capability to cause different problems, so its growth must be controlled. Utilization of bio-waste in the bioeconomy can be achieved with biosorption. In this study was investigated M. spicatum/alginate (5:1) biosorbent (MsA) for the removal of Pb(II) ions from aqueous solutions. MsA was characterized by Fourier transform infrared spectroscopy. The batch equilibrium was expressed by 5 isotherms and Redlich-Peterson isotherm model provided the best fit with the experimental data. Since, alginate-immobilized M. spicatum beads have superb Pb(II) uptake 200 mg/g they are appropriate cost-effective, environmental friendly biosorbent with potential application for continuous flow reactors. Managing and processing bio-waste must be deployed and integrated to meet the requirements of the sustainability. Keywords: bioeconomy, biosorption, aquatic weed, Myriophyllum spicatum, alginate, lead, Environmental sustainability